Associations Between Ultrasound‐Detected Synovitis, Pain, and Function in Interphalangeal and Thumb Base Osteoarthritis: Data From the Nor‐Hand Cohort. Issue 11 (29th October 2020) - Fjellstad, Caroline M.; Mathiessen, Alexander; Slatkowsky-Christensen, Barbara; Kvien, Tore K.; Hammer, Hilde B.; Haugen, Ida K.
Abstract : Objective: To explore whether ultrasound‐detected gray‐scale synovitis and power Doppler activity in the interphalangeal and first carpometacarpal (CMC1) joints are associated with pain and physical function in patients with hand osteoarthritis (OA). Methods: A total of 290 patients with hand OA underwent an ultrasound examination of the bilateral interphalangeal and CMC1 joints. Using logistic regression analyses with generalized estimating equations, we examined whether grade 0–3 gray‐scale synovitis and power Doppler activity were associated with pain in the same joint. Using linear regression analyses, we examined whether the degree of inflammation was associated with numeric rating scale and Australian/Canadian (AUSCAN) Osteoarthritis Hand Index hand pain, AUSCAN physical function, and grip strength scores. Analyses were made separately for interphalangeal and CMC1 joints, and adjusted for age, sex, body mass index, psychosocial factors, use of analgesics, and presence of osteophytes. Results: At joint level, increasing gray‐scale synovitis severity was associated with higher odds of pain upon palpation in both the interphalangeal (grade 2–3; odds ratio [OR] 3.17 [95% confidence interval (95% CI) 2.35, 4.28]) and CMC1 joints (grade 2–3; OR 4.40 [95% CI 2.10, 9.24]). Similar associations were found for power Doppler activity and joint pain in the previous 24 hours and 6 weeks. Power Doppler activity in CMC1 was also related to overall hand pain/physical function and lower grip strength. Conclusion: Inflammation in both the interphalangeal and CMC1 joints was associated with pain in the same joint. However, associations with hand pain, reduced physical function, and lower grip strength were only present for inflammation in the CMC1 joints, suggesting that lowering CMC1 inflammation is an important treatment target.